Crisis management competencies needed in a hospital setting during the COVID‐19 pandemic: A qualitative study of nurse leaders - Tarja Jääski; Hanne Talvio; Suvi Kuha; Outi Kanste (Wiley, 2024)
Abstract Aim To describe the crisis management competencies needed in a hospital setting during the COVID‐19 pandemic from the perspective of nurse leaders. Background The COVID‐19 pandemic generated many challenges for nurse leaders in hospitals, and management competencies are highlighted. However, there is little evidence available about nurse leaders' perceptions of the crisis management competencies needed in such situations. Methods A qualitative, descriptive, semi‐structured interview study of nurse leaders (n = 20) was conducted between June and October 2021 in one Finnish central hospital. The data were analysed using inductive content analysis. Results The analysis yielded five main categories of crisis management competencies needed in a hospital setting during the pandemic: interactive communication competence, psychological resource management competence, systematic and proactive organising competence, active networking abilities and practices and change management approach in crisis management. Conclusions Nurse leaders need new and different crisis management competencies in hospital organisations. The COVID‐19 pandemic changed the working culture of nurse leaders, as they faced challenges that needed knowledge and skills beyond their previous management competence. Implications for nursing management Additional training for nurse leaders in crisis management is needed. This training should reflect the competencies identified as necessary in crisis situations so that nurse leaders will be able to manage crisis situations effectively in future. Reporting method The Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist was used in reporting the findings. Patient or public contribution No patient or public contribution.